Clinical Presentations and Outcome of Acute Glomerulonephritis in Children (Bangladesh Medical Journal, 2019)
Acute post streptococcal glomerulonephritis (APSGN) is the most common type of acute glomerulonephritis (AGN) in childhood. It has not been studied well in Bangladesh. To evaluate the clinical characteristics, complications and outcome of Acute post streptococcal glomerulonephritis (AGN). the department of Pediatric Nephrology at Sir Salimullah Medical College and Mitford Hospital, Dhaka. A prospective study from April 2011 to March 2012 were conducted among the patients diagnosed as AGN in outdoor and indoor department. Hospital records of all 34 children who had been admitted to Sir Salimullah Medical College and Mitford Hospital were reviewed. All demographic, clinical, paraclinical data and consumed medications were obtained. Among 34 cases female and male ratio were 2.4:1; mean age of was 8.76 yrs. ± 2.5 SD and peak age 7.6. Etiology of AGN was post infectious glomerulonephritis (PIGN) 85.3%, ASO titer was raised in 88.2%, 41.2% had raised blood urea, and 32.4%raised serum creatinine level. All children presented with microscopic hematuria (100%), hypertension (100%), and edema (100%), other findings are fever (55.9%), oliguria (94.1%), abdominal pain (52.9%). History of sore throat and pyoderma was present in 41.2% and 44.1% cases respectively. Complications like hypertensive encephalopathy three (8.8%), urinary tract infection (UTI) one (2.9%) total seven (20%) were heart failure two (5.9%) and Acute kidney injury (AKI) one (2.9%), total seven (20%) were expired. Majority of cases manifest typically with edema, oliguria and hematuria. It usually has an uneventful course.Bangladesh Med J. 2019 Jan; 48 (1): 13-17